2018
DOI: 10.1007/s11554-017-0747-7
|View full text |Cite
|
Sign up to set email alerts
|

HD number plate localization and character segmentation on the Zynq heterogeneous SoC

Abstract: Automatic Number Plate Recognition (ANPR) systems have become widely used in safety, security, and commercial aspects. A typical ANPR system consists of three main stages: Number Plate Localization (NPL), Character Segmentation (CS), and Optical Character Recognition (OCR). In recent years, to provide a better recognition rate, High Definition (HD) cameras have started to be used. However, most known techniques for Standard Definition (SD) are not suitable for real-time HD image processing due to the computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The two stages utilize around 12% of the available resources in the selected platform. More details about the proposed HD NLP and CS stages by the authors can be found in [18,19].…”
Section: Proposed Methodologies and Algorithmsmentioning
confidence: 99%
“…The two stages utilize around 12% of the available resources in the selected platform. More details about the proposed HD NLP and CS stages by the authors can be found in [18,19].…”
Section: Proposed Methodologies and Algorithmsmentioning
confidence: 99%
“…The duality of morphological operations could be exploited by implementing a single architecture as hardware to perform dual functions using appropriate control logic for resource control. The work of [73] adopted [67] top-hat technique for plate feature extraction. Unlike [67], it carefully chose processing stages that consume more processing time to accelerate them on FPGA.…”
Section: Architecture For Morphological Filtersmentioning
confidence: 99%
“…Morphological open and image subtraction is used in place of spatial filters for edge detection [70–74]. Structuring elements used for morphological operations are designed based on the size of license plate and shape of characters.…”
Section: Alpr On Custom Computing Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…This method achieves a very high accuracy for detecting LP from one vehicle image with detection, precision and F-measure rates are 98.56%, 95.9%, and 97.19%, respectively. Ali Al-Zawqari et al [16], proposed an HD localization method for number plates. Firstly, the HD image resizes to SD image and then the features are extracted using morphological operations which then passed to CCA algorithm that identified white components using 4-connectivity.…”
Section: IImentioning
confidence: 99%